STUDI KOMPARATIF TENTANG MODEL PENGELOLAAN ZAKAT ANTARA RUMAH ZAKAT DAN BAITUL MAL ACEH - Muzakir Muzakir (AL-ILMU, 2023)
This study focuses on a comparative study of the zakat management model between Rumah Zakat and Baitul Mal Aceh. This study aims to determine the management of zakat carried out by Baitul Mal Aceh, also to find out the management of zakat carried out by Rumah Zakat Aceh and to find out the differences and similarities in the management of zakat between the two institutions. This study is qualitative research using a qualitative approach. The results of the study show that the management of zakat in Baitul Mal Aceh is carried out by implementing the best management, by conducting training, both inside and outside the city of Banda Aceh for human resources, also inviting third parties from Jakarta to assist and assess performance where there are still deficiencies so that there are always improve, evaluate each employee in order to find out how far the work that has been given can be carried out properly, all of this is seen from the annual evaluation. The management of zakat at RZ Aceh is to implement management that is carried out in accordance with the central command, everything that will be done has an SOP, and this applies to all RZ branches throughout Indonesia, such as muzakki who are always registered in the system. The rules that are implemented thus make the central RZ and branch RZ have a very strong relationship, where there is always control through the implemented system, every evening there is always a recap or data report by employees. While the differences and similarities in zakat management between the two institutions are both engaged in the collection, management and distribution. Besides that, other similarities are the principles of openness, volunteerism, integration, professionalism, and independence, the difference is in the field of programs, where Baitul Mal Aceh distributes its zakat through God's command in the Al-Quran Surah At-Taubah verse 60 while RZ distributes it through the program. Healthy Smiles, this program is engaged in public health, the Champion Smiles are engaged in education and the Mandiri Smiles are engaged in productive fields with efforts. In this BIG SMILE Indonesia, Rumah Zakat has also added the Smile Lestari program as a form of concern for the state of the environment. Keywords: Comparative Study, Zakat Management, Zakat, Baitul Mal Aceh